Cardiovascular, Pulmonary, and Neuropsychiatric Short- and Long-Term Complications of COVID-19 - Małgorzata Kobusiak-Prokopowicz; Katarzyna Fułek; Michał Fułek; Konrad Kaaz; Andrzej Mysiak; Donata Kurpas; Jan Aleksander Beszłej; Anna Brzecka; Jerzy Leszek (Cells, 2022)
Beginning with the various strategies of the SARS-CoV-2 virus to invade our bodies and manifest infection, and ending with the recent long COVID, we are witnessing the evolving course of the disease in addition to the pandemic. Given the partially controlled course of the COVID-19 pandemic, the greatest challenge currently lies in managing the short- and long-term complications of COVID-19. We have assembled current knowledge of the broad spectrum of cardiovascular, pulmonary, and neuropsychiatric sequelae following SARS-CoV-2 infection to understand how these clinical manifestations collectively lead to a severe form of the disease. The ultimate goal would be to better understand these complications and find ways to prevent clinical deterioration.